Reliability Analysis on the Bogie System at Indonesian High-Speed Trains in the Design Phase to Improve Service Quality - Warjito; Ansori, irfan; Shalahuddin, lukman; Bismantoko, Sahid (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
High-speed train (HST) Indonesia is rail-based public transportation which is planned to be implemented in Jakarta - Surabaya. To maintain the HST for excellence service, it is necessary to conduct a study on the quality of the service. This paper tries to approach the Bogie system quality service from the reliability perspective in the design phase. The steps taken to maintain continuity of service quality are to identify critical sub-systems/components that affect the decline in reliability, Risk Analysis, build Reliability Block Diagram (RBD) from sub-system/components that have been identified in the bogie system, calculate initial reliability based on RBD, develop designs to minimize the potential for a decline in reliability, and compile procedure for evaluating and re-calculation the value for the reliability of the bogie system. Reliability is targeted at 0.9, which means that all service quality designs must always make the reliability value above the target. This paper is expected to provide an overview of potential that may occur based on predictions of decreasing reliability values until the operating period ends. So that anticipation of minimizing the decline in the value of reliability can be done.